If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 15 + -5x = -7 + -12 Reorder the terms: 15 + 6x + -5x = -7 + -12 Combine like terms: 6x + -5x = 1x 15 + 1x = -7 + -12 Combine like terms: -7 + -12 = -19 15 + 1x = -19 Solving 15 + 1x = -19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 1x = -19 + -15 Combine like terms: 15 + -15 = 0 0 + 1x = -19 + -15 1x = -19 + -15 Combine like terms: -19 + -15 = -34 1x = -34 Divide each side by '1'. x = -34 Simplifying x = -34
| 4(x+3)=1+4x | | (9/4)x=18 | | -10x-14y=27 | | (3x-5)2+30x-34=0 | | 5x=12-(-8) | | hx=41 | | 4x+19=2x+71 | | 4y+8=72 | | 9-(9x)-5-(6x)=7 | | (3x-5)2+30-34=0 | | 71x-51=16x+6 | | 4*x-1/7=2x | | 3n^2+19n+24=4 | | 5s-35t-15= | | 5x+8y=70 | | 2+1.25f=10-2.25f | | 7+4q-15=24 | | K=-x^2+18x | | 20x+5=13x-16 | | 12=14y | | 5(2a+7)+16+4a= | | -4(n+7)=8 | | -(p-36)=-25 | | 69=14+5j | | 50b+190=1330 | | 7n^2+32n+16=0 | | (x-2)(x+3)=-4(x+3) | | cos(x+15)=0.5 | | g(x)=3x-5x-1 | | w-8.3=-9 | | 3*(x-7)=-21+3x | | 18-[1+6y-4(y+3)]=-5(3y-4)-[6(y-1)-16y+15] |